Zmienność nasion Pinus sylvestris L. z uwzględnieniem barwy okrywy nasiennej - Banach, Jacek; Pańczyk, Beata; Skrzyszewska, Kinga (Leśne Prace Badawcze, 2021)
The aim of this work was to compare the variability of Scots pine Pinus sylvestris L. seeds collected in three forest sites in the Radomsko Forest District. This comparison was mainly based on viability and weight of 1000 seeds, which was then used to calculate seed value for each sample. Furthermore, seed size was assessed by measuring their length, width and area, using the WinSeedle software. All evaluated samples belonged to viability class I. Seeds originating from the Bąkowa Góra forest range were characterized by the highest weight, best viability and the largest size. In the next stage of our research, we performed an analysis of variability parameters taking the colour of the seed coat into consideration. For this analysis, the seeds were divided into three colour groups (fawn, brown, black) and their vitality and weight were assessed separately. The share of fawn seeds was 9.4%, brown 39.6% and black 50.9%. The weight of 1000 seeds and seed size parameters of fawn seeds were slightly higher than those of the black and brown seeds. The fawn and black seeds belonged to vitality class I, while brown seeds belonged to vitality class II. Despite the observed variability, seeds belonging to different colour groups did not show statistically significant differences in other measured parameters. The factor with the greatest impact on the seed parameters was the site of origin, which differed in their forest site type. Larger and heavier seeds came from the broadleaved forest site compared to the coniferous forest sites.